2015
DOI: 10.1371/journal.pone.0131014
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Disability among the Elderly in Xiamen of China: A Representative Sample Survey of 14,292 Older Adults

Abstract: BackgroundThe unprecedented number of elderly individuals in China presents a serious public health challenge. Limited data are available on the prevalence of disability or factors resulting in disability among the elderly in China.ObjectiveWe aimed to assess the prevalence of disability and related risk factors among the elderly of Xiamen, China.MethodsA cross-sectional study was performed on individuals who were ≥60 years of age. The subjects were recruited by multi-stage sampling; a total of 14,292 valid qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
20
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 29 publications
4
20
1
1
Order By: Relevance
“…From our data, older adults living with children at baseline reported lower cognitive function (mental status) at both baseline and follow up. Findings that living with children was associated with physical disabilities were reported in other studies [41][42][43]. This pattern may be attributed to the fact that older adults with physical or cognitive impairment tend to live with their children for support.…”
Section: Discussionsupporting
confidence: 58%
“…From our data, older adults living with children at baseline reported lower cognitive function (mental status) at both baseline and follow up. Findings that living with children was associated with physical disabilities were reported in other studies [41][42][43]. This pattern may be attributed to the fact that older adults with physical or cognitive impairment tend to live with their children for support.…”
Section: Discussionsupporting
confidence: 58%
“…Nesse Contexto, uma revisão sistemática com metanálise que avaliou a capacidade funcional de idosos brasileiros, encontrou entre os estudos somente 8,7% objetivando os idosos longevos e todos os estudos eram baseados em informações autorreferidas para a capacidade funcional 17 . Ao analisar os dados sociodemográficos, ressalta-se a feminilização da população estudada, em concordância com a literatura [18][19] , que pode ser explicada pelas diferentes características de mortalidade entre os sexos 20 . Ainda, a maioria mora acompanhada (o), são viúvas(os), sabem ler/escrever e tem renda de um a dois salários mínimos.…”
Section: Discussionunclassified
“…Converging results were obtained by Chen et al who showed that disability was associated with old age, single marital status, a sense of isolation and bad mood [44]. Holwerda et al in a prospective cohort study showed that the feeling of loneliness and social isolation were the main risk factors for increased mortality among older men [45].…”
Section: Discussionmentioning
confidence: 93%